Effect of gender on late-onset multiple sclerosis - Bove, Riley M; Healy, Brian; Augustine, Ann; Musallam, Alexander; Gholipour, Taha; Chitnis, Tanuja (Multiple sclerosis, 2012)
Objectives: We aimed to examine the incidence and disease course of late-onset multiple sclerosis (LOMS) compared with adult-onset MS (AOMS) in our clinic cohort, stratified based on gender and race, since both have been reported as important modifiers of disease outcomes in MS. Methods: Patients with LOMS and AOMS were compared in terms of demographic characteristics and disease course characteristics. Combined effects were investigated with a logistic regression model. Time from disease onset to sustained Expanded Disability Status Scale (EDSS) score of 6 was investigated using an extension of log-rank test appropriate for interval-censored data. Results: Some 7.96% of 4273 patients studied had an onset of MS after the age of 50 years (LOMS), and 1.33% experienced an onset after age 60. Progressive onset was more common in LOMS relative to AOMS. The proportion of women with progressive-onset disease was similar in AOMS and LOMS. Time to EDSS 6 was delayed in AOMS females compared with males; however, it was similar between males and females in the LOMS group. Conclusions: Women with LOMS have a different trajectory in terms of disease progression than women with AOMS. The effect of menopause combined with race/ethnicity on the MS disease course requires further investigation.